Enhancing the photodetection property of CdSe thin films via thermal evaporation technique: role of substrate temperature. (1st May 2022) - Sathish Kumar, S; Valanarasu, S; Gunavathy, K V; Vinoth, S; Haunsbhavi, Kumar; Alagarasan, Devarajan; Deva Arun Kumar, K; Ubaidullah, Mohd; F. Shaikh, Shoyebmohamad; Pandit, Bidhan
Abstract: The current work investigates the influence of the substrate temperature on the photodetection capability of cadmium selenide (CdSe) thin films deposited through economically viable thermal evaporation technique on glass substrates. The substrate temperature varied from room temperature (30 °C to 250 °C). The existence of a single-phase of hexagonal structured CdSe was established from XRD patterns with dominant peaks along the (002) plane in all the samples. The SEM micrographs show the homogeneous surface of the films without any pinholes. The bandgap of the films was found to vary with the variation in the substrate temperature and the sample fabricated at 200 °C substrate temperature showed a bandgap of 2.00 eV. The light-dependent electrical analysis is also made to reveal the photodetection capability of the deposited CdSe films. The 200°C deposited CdSe film exhibits a higher responsivity of 8.07 × 10 −2 A W −1 and a maximum detectivity of 6.66 × 10 9 Jones. The external quantum efficiency (EQE) was found to rise with the substrate temperature and a maximum value of 18.8% for the 200 °C deposited sample. The observed rise and decay times show a rapid response when the incident light intensity is changed from 1 to 5 mW cm −2 .